2010
DOI: 10.3847/aer2010017
|View full text |Cite
|
Sign up to set email alerts
|

Daytime School Guided Visits to an Astronomical Observatory in Brazil

Abstract: This article analyzes the activity Daytime School Guided Visits at an astronomical observatory in Brazil with pupils from primary school. The adopted research methodology relied on questionnaire applications and semistructured interviews. The objectives were to identify the influences of the visits on learning of astronomical concepts and on pupils' motivation toward science. This study showed that it is difficult for children to understand scale distances in the Solar System and beyond. In order to cope with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Likewise, in the study of Petrie (2013) with the students and family groups participating in the planetarium program, they stated that the students love these programs and will be interested in astronomy in the future. In the study of Colombo, Silva and Aroca (2010), they investigated the effect of planetariums in teaching astronomy concepts and increasing motivation among students and as a result, they emphasized the increasing importance given to science centers.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, in the study of Petrie (2013) with the students and family groups participating in the planetarium program, they stated that the students love these programs and will be interested in astronomy in the future. In the study of Colombo, Silva and Aroca (2010), they investigated the effect of planetariums in teaching astronomy concepts and increasing motivation among students and as a result, they emphasized the increasing importance given to science centers.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the Solar System is also featured in the National Curriculum of England, as well (Department for Education, 2013). Research on students and teachers learning about the Solar System in Brazil (Colombo, Aroca, & Silva, 2010), the Netherlands (Henze, Van Driel, & Verloop, 2008), England (Sharp & Kuerbis, 2006), and Japan (Suzuki, 1998) suggests that these ideas are important across cultural contexts.…”
Section: Introductionmentioning
confidence: 97%
“…When we consider the literature, it is seen that the result of the research is supported and the use of different methods, materials and environments in teaching astronomy increases the success levels of the participants in different age groups (Colombo, Aroca, & Silva, 2010;Frede, 2008;Kucukozer, Bostan & Isildak, 2010;Kucukozer, Korkusuz, Kucukozer, & Yurumezoglu, 2009;Ndihokubwayo, Uwamahoro, & Ndayambaje, 2018;Trumper, 2006;Trundle, Atwood, & Christopher, 2002, 2006Turk, 2010). For example, Trundle et al (2007) found that there was a significant increase in students' post-test results in their experimental research with 4th-grade students.…”
Section: Discussionmentioning
confidence: 99%